Khellin and visnagin differentially modulate AHR signaling and downstream CYP1A activity in human liver cells - Vrzal, Radim; Frauenstein, Katrin; Proksch, Peter; Abel, Josef; Dvorak, Zdenek; Haarmann-Stemmann, Thomas (PloS one, 2013)
Khellin and visnagin are two furanochromones that can be frequently found in ethnomedical formulations in Asia and the Middle East. Both compounds possess anti-inflammatory and analgesic properties, therefore modern medicine uses these compounds or structurally related derivatives for treatment of vitiligo, bronchial asthma and renal colics. Despite their frequent usage, the potential toxic properties of visnagin and khellin are not well characterized up-to-now. Many natural compounds modulate the expression and activity of cytochrome P450 1A1 (CYP1A1), which is well-known to bioactivate pro-carcinogens. The expression of this enzyme is controlled by the aryl hydrocarbon receptor (AHR), a ligand-activated transcription factor and regulator of drug metabolism. Here, we investigated the influence of both furanochromones on AHR signaling in human HepG2 hepatocarcinoma cells and primary human hepatocytes. Both compounds transactivated xenobiotic response element (XRE)-driven reporter gene activity in a dose-dependent manner and induced CYP1A1 transcription in HepG2 cells and primary hepatocytes. The latter was abolished in presence of a specific AHR antagonist. CYP1A enzyme activity assays done in HepG2 cells and primary hepatocytes revealed an inhibition of enzyme activity by both furanochromones, which may become relevant regarding the metabolism of xenobiotics and co-administered therapeutic drugs. The observed induction of several other members of the AHR gene battery, whose gene products are involved in regulation of cell growth, differentiation and migration, indicates that a further toxicological characterization of visnagin and khelllin is urgently required in order to minimize potential drug-drug interactions and other toxic side-effects that may occur during therapeutic usage of these furanochromones.
Keywords: hepatocyty; Gene Expression Regulation; exprese genu; Gene Expression; receptory aromatických uhlovodíků; Cell Line; Enzyme Activation; khelin; Cytochrome P-450 CYP1A1; reportérové geny; Khellin; signální transdukce; cytochrom P-450 CYP1A1; Signal Transduction; Hepatocytes; lidé; aromatické hydroxylasy; Humans; Aryl Hydrocarbon Hydroxylases; regulace genové exprese; aktivace enzymů; buněčné linie; Genes, Reporter; Receptors, Aryl Hydrocarbon